Integrative analysis of network pharmacology and proteomics to identify key targets of Tuomin-Zhiti-Decoction for allergic rhinitis - Cheng, Jinjun; Zhang, Meiling; Zheng, Yanfei; Wang, Ji; Wang, Qi (Journal of ethnopharmacology, 2022)
Allergic rhinitis (AR) is one of most prevalent disease and it is urgent need to develop new drug. Tuomin-Zhiti-Decoction (TZD) is a traditional medicinal compound consisting of eleven different herbs and has a significant effect on AR, yet its underlying mechanism is still unknown. The aim of this study was to confirm the anti-AR effects and the underlying mechanism of TZD. Integrative analysis of network pharmacology and proteomics to explore the common mechanism of TZD treating AR. Mice were subjected to serial intranasal challenge with ovalbumin (OVA), we examinated the nasal symptoms, histopathology and Th1/Th2-related cytokines after TZD treatments. Active compounds, potential targets and underlying mechanisms of TZD against AR were systematically clarified by integrating network pharmacology and proteomics analysis. Then we validated the binding affinity between the key potential targets and matching active compounds using molecular docking evaluation. TZD controlled allergy by reduction of OVA-specific immunoglobulin E (IgE) and histamine release. In nasal tissue, TZD decreased nasal rubbing, sneezing and reduced AR-induced damage to nasal mucosa, accordingly, the nasal symptoms were also clearly ameliorated. Moreover, TZD modulated the balance of Th1/Th2/Th17. The proteomics analysis recognized 41 differentially expressed proteins (DEPs). Integrative analysis of network pharmacology and proteomics, we found IL-6 and CD40 could be potential protein targets of TZD aganist AR, quercetin and wogonin may play more effective roles in AR. Active core compounds of TZD could bind closely to the key targets by molecular docking. TZD may have therapeutic potential for treating AR, integrating analysis of network pharmacology and proteomics uncovered the underlying mechanism and targets of TZD, which provides a scientific method for the sensible development of traditional Chinese medicine. [Display omitted] •Integrating analysis of network pharmacology and proteomics uncovered the underlying mechanism and targets of TZD.•The combined methodology provides a scientific method for the sensible development of traditional Chinese medicine.•TZD may have therapeutic potential for treating AR.•CD40 and IL6 are the main targets.•Quercetin and wogonin may play more effective roles in AR.